2015
DOI: 10.1177/0004563215580000
|View full text |Cite
|
Sign up to set email alerts
|

The effect of storage conditions on sample stability in the routine clinical laboratory

Abstract: 'Add-on' tests can only be safely performed on a proportion of routine analytes. For some analytes, storage conditions affect their suitability for delayed analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 2 publications
4
9
0
Order By: Relevance
“…With regard to bilirubin, the results obtained by us are consistent with the results of Kift et al [35], showing that the concentration of bilirubin in the serum stored at the temperature of the refrigerator remains approximately constant, which confirms the occurrence of photo degradation of this parameter in the case when the tested material is exposed to light, as a result of geometric isomerization and oxidation caused by photons. In addition, the above reactions proceed faster at higher temperatures.…”
Section: Effect Of Storage At Room Temperature and Refrigerationsupporting
confidence: 91%
See 1 more Smart Citation
“…With regard to bilirubin, the results obtained by us are consistent with the results of Kift et al [35], showing that the concentration of bilirubin in the serum stored at the temperature of the refrigerator remains approximately constant, which confirms the occurrence of photo degradation of this parameter in the case when the tested material is exposed to light, as a result of geometric isomerization and oxidation caused by photons. In addition, the above reactions proceed faster at higher temperatures.…”
Section: Effect Of Storage At Room Temperature and Refrigerationsupporting
confidence: 91%
“…It is obvious that exposure to light could significantly decrease bilirubin concentration, which was confirmed by the results of the present study. Thus, the samples for determination of bilirubin concentration should be rather stored much shorter on an illuminated countertop at room temperature, than in the dark at 4 • C. The obtained results are consistent with the results of Kift et al [35], which show that the concentration of bilirubin in the serum stored at refrigerator temperature remains approximately constant. The same authors also concluded that the concentration of total protein increases along with the increase of temperature [35].…”
Section: Effect Of Storage At Room Temperature and Refrigerationsupporting
confidence: 89%
“…Kift et al 14 examined the effect of storage conditions on sample stability and showed that triglycerides and HDL-c concentrations were increased after 16 hours in room temperature (≈ 20°C), but total cholesterol concentration remained stable. However, other authors reported that total cholesterol, triglycerides and HDL-c remain stable even after 24 hours up until 30°C, while glucose concentrations usually decreases progressively after six hours in room temperature 15,16 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study with open serum samples kept at room temperature for 16 hours found an 8.7 mmol/L mean variation for Na+, 0.24 mmol/L for K + and 6.8 mmol/L for Cl - ( 1 ). Nauck et al found serum Na + concentration increased about 13% in 0.5 mL samples and 3% in 2 mL samples kept opened at 22 şC for 24 hours; the evaporation rate was smaller (5%) for 0.5 mL samples kept opened and refrigerated for 1 day ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Evaporation is a well-known cause of variation in analyte concentration, especially in automated environments ( 1 ), influenced by sample volume, tube type, storage conditions and surface area ( 2 ). Storage temperature is also recognized as a significant factor in sample stability, particularly for potassium (K + ); at low temperatures, the Na + /K + ATPase is inhibited and K + tends to leave the cells ( 3 ).…”
Section: Introductionmentioning
confidence: 99%